A bovine lactoferricin-lactoferrampin-encoding Lactobacillus reuteri CO21 regulates the intestinal mucosal immunity and enhances the protection of piglets against enterotoxigenic Escherichia coli K88 challenge. (1st January 2021) - Xie, Weichun; Song, Liying; Wang, Xueying; Xu, Yigang; Liu, Zengsu; Zhao, Dongfang; Wang, Shubo; Fan, Xiaolong; Wang, Zhaorui; Gao, Chong; Wang, Xiaona; Wang, Li; et al.
ABSTRACT: Enterotoxigenic Escherichia coli (ETEC) is an important cause of diarrhea in human and animal. To determine the mechanism of a bovine lactoferricin-lactoferrampin (LFCA)-encoding Lactobacillus reuteri CO21 (LR-LFCA) to enhance the intestinal mucosal immunity, we used a newborn piglet intestine model to study the intestinal response to ETEC. Pigs were chosen due to the anatomical similarity between the porcine and the human intestine.4-day-old piglets were orally administered with LR-LFCA, LR-con ( L. reuteri CO21 transformed with pPG612 plasmid) or phosphate buffered saline (PBS) for three consecutive days, within 21 days after these treatments, we found that LR-LFCA can colonize the intestines of piglets, improve the growth performance, enhance immune response and is beneficial for intestinal health of piglets by improving intestinal barrier function and modulating the composition of gut microbiota. Twenty-one days after, piglets were infected with ETEC K88 for 5 days, we found that oral administration of LR-LFCA to neonatal piglets attenuated ETEC-induced the weight loss of piglets and diarrhea incidence. LR-LFCA decreased the production of inflammatory factors and oxidative stress in intestinal mucosa of ETEC-infected piglets. Additionally, LR-LFCA increased the expression of tight junction proteins in the ileum of ETEC-infected piglets. Using LPS-induced porcine intestinal epithelial cells (IPEC-J2) in vitro, we demonstrated that LR-LFCA-mediated increases in the tight junction proteins might depend on the MLCK pathway; LR-LFCA might increase the anti-inflammatory ability by inhibiting the NF-κB pathway. We also found that LR-LFCA may enhance the antioxidant capacity of piglets by activating the Nrf2/HO-1 pathway. This study demonstrates that LR-LFCA is effective at maintaining intestinal epithelial integrity and host homeostasis as well as at repairing intestinal damage after ETEC infection and is thus a promising alternative therapeutic method for intestinal inflammation.